Practical boundary surveying legal and technical principles - Gay, Paul (Springer International Publishing, 2015)
This guide to boundary surveying provides landowners, land surveyors, students and others with the necessary foundation to understand boundary surveying techniques and the common legal issues that govern boundary establishment. Boundary surveying is sometimes mistakenly considered a strictly technical discipline with simple and straightforward technical solutions. In reality, boundary establishment is often a difficult and complex matter, requiring years of experience and a thorough understanding of boundary law. This book helps readers to understand the challenges often encountered by boundary surveyors and some of the available solutions. Using only simple and logically explained mathematics, the principles and practice of boundary surveying are demystified for those without prior experience, and the focused coverage of pivotal issues such as easements and setting lot corners will aid even licensed practitioners in untangling thorny cases. Practical advice on using both basic and advanced instruments is included, alongside clear explanations of the legal elements that impact boundary establishment. Because many modern surveys are resurveys of existing boundaries, which may have been created a century or more ago, this book discusses the historical techniques of boundary surveying so the modern surveyor will understand how to follow in the footsteps of the original surveyor. For those who desire a more in-depth treatment of the mathematical aspects of boundary surveying, the Appendix includes the underlying theory and many examples of typical calculations performed by boundary surveyors.